Shift-Left Testing in the Software Testing Life Cycle: Evidence from the Ruang Murid Application on Time Efficiency and Software Quality - Agung Enrico; Ana Kurniawati (International Journal of Management Science and Information Technology, 2026)
This study investigates the implementation of Shift-Left Testing within the Software Testing Life Cycle (STLC) and its implications for testing time efficiency and software quality in the Ruang Murid application. A quantitative case study design was applied using testing records, observation, documentation, and questionnaire data collected from the development team, including Software Quality Assurance staff, developers, and the project manager. Data were analysed using SPSS through validity and reliability testing, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. The results show that after the adoption of Shift-Left Testing, the number of detected bugs increased by 54.39%, indicating broader and earlier defect discovery during the development cycle rather than a decline in product quality. Bug rate rose from 1.9 to 2.9 bugs per KLOC, while defect rate increased from 4.2% to 7.1%, both of which remained within acceptable quality thresholds. In addition, defect leakage was recorded at 10.37%, test coverage and test execution rate each reached 100%, and the test case pass rate was 50.51%. These findings suggest that the earlier involvement of the SQA team improved defect visibility, expanded testing coverage, and strengthened quality control across development stages, although further improvements are still needed to increase pass stability and overall testing confidence.